2016
DOI: 10.1242/jeb.136820
|View full text |Cite
|
Sign up to set email alerts
|

Object approach computation by a giant neuron and its relation with the speed of escape in the crab Neohelice

Abstract: Upon detection of an approaching object, the crab Neohelice granulata continuously regulates the direction and speed of escape according to ongoing visual information. These visuomotor transformations are thought to be largely accounted for by a small number of motion-sensitive giant neurons projecting from the lobula (third optic neuropil) towards the supraesophageal ganglion. One of these elements, the monostratified lobula giant neuron of type 2 (MLG2), proved to be highly sensitive to looming stimuli (a 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In contrast, the apparently unique MLG2 neuron, with its receptive field that encompasses the whole 360 deg, was found to respond to stimuli approaching from anywhere around the crab, and to encode looming information for images expanding beyond 35 deg. Using a wide variety of stimulus dynamics, we found that the MLG2 neuron faithfully encodes the angular velocity of looming stimuli, and thus conveys the information that is used by the animal to continuously adjust its running speed (Oliva and Tomsic, 2016).…”
Section: The Visual System and Motion Detection Of Crabsmentioning
confidence: 99%
“…In contrast, the apparently unique MLG2 neuron, with its receptive field that encompasses the whole 360 deg, was found to respond to stimuli approaching from anywhere around the crab, and to encode looming information for images expanding beyond 35 deg. Using a wide variety of stimulus dynamics, we found that the MLG2 neuron faithfully encodes the angular velocity of looming stimuli, and thus conveys the information that is used by the animal to continuously adjust its running speed (Oliva and Tomsic, 2016).…”
Section: The Visual System and Motion Detection Of Crabsmentioning
confidence: 99%
“…However, the response of these two cells to looming stimuli was very different. On one hand, the MLG2 neuron increases the firing rate according to the dynamic of image expansion (Oliva et al, 2007 ; Oliva and Tomsic, 2016 ). This is illustrated in the intracellularly recorded trace of Figure 3B .…”
Section: Resultsmentioning
confidence: 99%
“…The cell morphologies shown in panels ( A,F ) are from Medan et al ( 2007 ). Data shown in panels ( B,D ) have been modified from Oliva and Tomsic ( 2016 ). Data in panels ( G,I ) have been modified from Oliva ( 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Escape behaviors to looming stimuli have been particularly well investigated in two other family of arthropods: grasshoppers and crabs. In contrast to Drosophila, the visual inputs to looming detection neurons in these animals are not thought to be directionally selective Gabbiani 2010, 2012;Medan et al 2007;Oliva and Tomsic 2016). Yet, the computations carried out in Drosophila, grasshoppers, and crabs appear very similar at the behavioral level Oliva and Tomsic 2012;von Reyn et al 2014).…”
Section: Discussionmentioning
confidence: 99%